Economic burden of diabetic foot ulcer: a case of Iran - Reza Hashempour; SeyedHadi MirHashemi; Fariba Mollajafari; Soheila Damiri; Ali ArabAhmadi; Behzad Raei (BMC, 2024)
Abstract Background Diabetic foot ulcer (DFU) is known as a serious complication of diabetes mellitus in patients with diabetes, imposing heavy medical costs on healthcare systems due to its chronic nature. patients with severe diabetic foot ulcer are often disabled to work, and some of them may even die, leading to associated productivity losses. Since no previous study has investigated the economic burden of DFU in Iran, this study is to estimate the economic burden of diabetic foot disease in Iran. Methods In this descriptive cross-sectional study, randomly selected samples consisted of 542 patients with DFU, hospitalized in the hospitals of Shahid Beheshti University of Medical Sciences. The demographic profile and cost data used in this analysis were derived from a researcher-designed checklist. Lost productivity was calculated based on Human Capital Approach, and the total economic cost of DFU was determined using patient-level data on costs and prevalence data from the global burden of diseases reports. All analyses were performed using SPSS software (Version 23), and Microsoft Excel (Version 19). Results The economic burden of DFU in Iran in two scenarios of discounting future costs and not discounting them was about $8.7 billion and $35 billion, respectively (about 0.59 and 2.41% of GDP). 79.25% of the estimated costs in this study were indirect costs and productivity losses, of which 99.34% (7,918.4 million Dollars) were productivity losses due to premature death. 20.75% (2,064.4 million dollars) of the estimated costs in this study were direct costs. The average length of stay (LOS) was 8.10 days (SD = 9.32), and 73.3% of patients recovered and were discharged after hospitalization and 7.6% died. The majority of the costs are imposed on the age group of 60-69 year (53.42% of the productivity lost due to hospital length of stay, 58.91% of the productivity lost due to premature death & 40.41% of direct costs). Conclusions DFU represents a heavy burden to patients, Iran's health system, and the economy. Early prevention strategies need to be prioritized in making public health policies. These policies and decisions can be in the area of changing lifestyle, health education, changing people's behavior, and encouraging physical activity that targeted high-risk populations in order to reduce the prevalence of diabetic foot and resulting substantial economic burden.